Prosthetic Joint Infection Microorganism Pattern and Risk Factor Profile: A Single Center Study - Fahreza Hilmy; Yoshi Pratama Djaja; Anggaditya Putra; Jamot Silitonga; Ludwig Andribert Pontoh (Indonesian Hip and Knee Society (IHKS), 2020)
Introduction: Prosthetic joint infection (PJI) is a serious complication especially following arthroplasty surgeries. The outcome of these cases is affected by the pattern of infection, causative microorganism, and antibiotic resistance. This study was aimed to evaluate the prevalence of PJI, distribution of causative microorganism, antibiotic resistance, and risk factor profiling.Methods: A retrospective review was performed by arthroplasty registry evaluation from 2008-2018, followed by a medical record review and patient interview. Distribution of causative microorganisms, antibiotic resistance patterns, and the onset of infection was extracted. Risk factor evaluation was performed by assessing preoperative (age, body mass index (BMI), frailty index) and perioperative parameters (duration of surgery, number of previous surgeries, the interval between those surgeries). Results: Seventeen patients were diagnosed with PJI (13 hip and 4 knees), with a prevalence of 1.56% and 1.77% respectively. The most common causative organism was Staphylococcus aureus and Escherichia coli with multiple antibiotic resistance patterns. These infections mostly occurred in patients with the age of 40-60 years, BMI 30kg/m2, and pre-operative frailty index of 4. The perioperative risk factor was the duration of surgery for more than 3 hours, have undergone more than 3 surgeries with an average surgical interval of 2 months.Conclusions: The prevalence of PJI in this series was 1.56% in hip and 1.77% in the knee. The risk factor profile showed that most cases have high BMI, prolonged duration of surgery, and a high number of previous surgeries within a short interval.